Визуализация обонятельной щели - Носова, Я. В.; Шушляпина, Н. О.; Носова, Т. В. (НТУ "ХПИ", 2015)
Статья посвящена проблеме визуализации обонятельной щели. Изучение процесса восприятия и идентификации пахучих веществ необходимо для многих отраслей жизнедеятельности человека: от парфюмерии и рекламного бизнеса до оборонной промышленности. Обонятельная щель является одной из основных составляющих частей обонятельного анализатора, поэтому визуализация ее внутренних структур представляет собой важную задачу для исследования процесса восприятия запахов. Рассмотрены основные методы визуализации верхних дыхательных путей.

Purpose of work is consider possibilities of visualization of the olfactory slit for diagnostics of pathological conditions of the upper respiratory tract. The objectives of the work are the analysis of hardware and imaging techniques structures olfactory analyzer. Traditionally introscopic diagnosis of diseases of the nasal cavity was performed by X-ray. At the present stage, to determine the configuration of the upper respiratory tract is expedient to use X-ray data spiral computed tomography. Visualization of the olfactory slit by digital volume tomography is recommended as the most informative methods in the complex preoperative examination of patients with diseases of the nose and paranasal sinuses, which are planned surgical intervention in the olfactory slit. Imaging Systems of computer tomographs often have modules dimensional (2D), as well as space (3D) processing and display of data. In the 2D module implements the functionality of building multiplanar reconstruction and segmentation of tomographic images on individual anatomical structures. When forming tomographic images reconstructed by means of spiral CT region seems set of elementary volumes - voxels (voxel - volume element), each of which is characterized by the density in Hounsfield units NU. Thus, the presented methods and imaging hardware olfactory slit through which is carried a correct diagnosis of pathological conditions of the upper respiratory tract, in particular the olfactory apparatus. considered methods make it possible to develop algorithms to generate optimal endosurgical access based on process modeling of of surgical interventions and post-operative monitoring of the patients.
Visualization of the olfactory slit
Keywords: верхние дыхательные пути; обонятельный анализатор; восприятие запахов; клетки базальные; обонятельная дисфункция; smell; nose; olfactory slit; tumor cells basal